Tramandare la memoria sociale del Novecento L'archivio di Gino Cerrito presso la Biblioteca di scienze sociali dell'Università di Firenze. Atti della giornata di studio (Firenze, 21 novembre 2019) - Boldrini, Enrica; Conigliello, Lucilla (Strumenti per la didattica e la ricerca, 2021)
The volume contains the proceedings of the conference Tramandare la memoria sociale del Novecento (Florence, 11.21.2019), on the occasion of presenting Gino Cerrito's archive. owned at present by the Social sciences library, University of Florence. Cerrito papers represent a primary source to investigate social movements in the XX century, especially anarchism, with particular reference to the War of Spain and to anarchical syndacalism between the two world wars. The project gave the opportunity to focus on the main issues concerning the preservation of the social memory of the XX century among experts and professionals. Historians, archivists, librarians, professors, association members and officers of the heritage preservation institutions discuss the problems and strategies confronting its conservation and enhancement. Investigate recent past requires a molteplicity of sources, beyond paper and through a great variety of expressions and media. And movements and their archives present peculiarities. Technical and political issues are considered, and a variety of cases and initiatives relating to archives dedicated to social movements and associations.